The Effect of Out-Of-School Learning Environments on Students' Mental Models and Academic Achievements: The Case of the Tropical Ecosystem - Türkmen, Hakan (International Journal Pedagogy of Social Studies, 2023)
The aim of this study is to examine the effects of out-of-school learning environments (İzmir Natural Life Park) on the development of secondary school 7th-grade students' mental models about tropical environments and their academic achievement. The research was carried out with the participation of 57 students studying in the 7th grade at a public school in Izmir. During the discovery phase of the lesson plans prepared under the 4E teaching model, lessons were taught under the conservative curriculum with the control group (27), and a visit to the Izmir Natural Life Park Tropical Center was made with the experimental group (30). To compare the mental model developments and academic achievements of the experimental and control groups, the Achievement test consisting of twelve multiple-choice questions with drawings before and after the research was applied in the study conducted in a mixed design. In addition, an interview form consisting of five open-ended questions was given to the experimental group to get their opinions after the trip. The data obtained from the Achievement Test were subjected to independent groups t-test and it was determined that there was a statistically significant difference between the two groups. This result proves that out-of-school learning environments are used in a planned way, they positively affect students' learning and increase their academic success. The preliminary and final drawings of the mental model and their explanations were analyzed under the guidance of the ‘Development Level Evaluation Table’ determined by the researchers. Accordingly, it is seen that students' perspectives and perceptions about the tropical ecosystem develop after the application. In particular, it is seen that the explanations and drawings of the experimental group are customized, the diversity of life is deepened specific to tropical environments, and the connections are elaborated. In the interview questions applied after the trip, the students stated that they contributed to their learning by observing, experiencing, and enjoying the tropical environment during their visit.